The Evolving Landscape of Immunotherapy-Based Combinations for Frontline Treatment of Advanced Renal Cell Carcinoma - Amin, Asim; Hammers, Hans (Frontiers in Immunology, 2019)
Insights into the biology of advanced renal cell carcinoma (aRCC) and the development of agents targeting the vascular endothelial growth factor (VEGF) pathway have positively impacted the outcomes for patients with aRCC. With the recent approval of the dual immune checkpoint inhibitors (ICIs), nivolumab and ipilimumab, by the U.S. Food and Drug Administration (USFDA), and the European Medicines Agency (EMA), the era of VEGF monotherapy for untreated aRCC appears to be coming to an end for patients with access to the combination therapy. The frontline treatment options for renal cell carcinoma are evolving rapidly and will lead to the approval of other combination immunotherapies—especially those with VEGF inhibitors. Here we review the clinical data for dual immune checkpoint inhibition with nivolumab plus ipilimumab as well as the emerging data for ICI plus VEGF inhibitor combinations and discuss the challenges these will pose for the clinical practitioner.